The effects of audio stimuli on auditory-evoked potential in normal hearing Malay adults - Ibrahim, Ibrahim Amer; Ting, Hua-Nong; Moghavvemi, Mahmoud (International Journal of Health Sciences, 2018)
Objectives: The hearing process in the brain is very complicated and hard to solve. However, an understanding of the hearing process is an essential issue and needed in many rehabilitation or treatment applications. This study investigates and compares the effects of simple and complex sounds on latency and amplitude of various event-related potential (ERP) components to male ethnic Malay adults. Comparisons were made with previous studies. Materials and Methods: Simple and complex sounds were used (pure tones and the naturally produced Malay consonant–vowels [CVs]) to evoke the cortical auditory-evoked potential (CAEP) signals. Moreover, this study analyzed the influence of related CAEP components that are distinct to the selected population and determined which of the ERP components among (CAEP) components is most affected by the two distinct stimuli. Moreover, the study used classification algorithms to discover the ability of the brain in distinguishing CAEP evoked by stimuli contrasts. Results: The results showed some resemblance between our results and ERP waveforms outlined in previous studies conducted on native speakers of English. On the other hand, it was also observed that the P1 and N2 had a significant effect in amplitude due to different stimulus. Conclusion: The results show high classification accuracy for the brain to distinguish auditory stimuli. Moreover, the results indicated some resemblance to previous studies conducted on native English speakers using similar tones and English CV stimuli. However, the amplitudes and latencies of the P1 were found to have a significant difference due to stimuli complexity.